Science Forum 2016: Summary Report - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
This Summary Report of Science Forum 2016 (SF16) held from 12-14 April 2016 in Addis Ababa summarizes the Plenary and Breakout sessions of the event. The objective of SF16 was to reassess the pathways for agricultural research to stimulate inclusive development of rural economies in an era of climate change. Nearly 200 participants from around the globe representing the CGIAR and research organizations attended SF16.